Advances in relational frame theory : research and application - Roche, Bryan, 1969-; Dymond, Simon (New Harbinger Publications, 2013)
"As acceptance and commitment therapy (ACT) increases in popularity among clinicians, it becomes more and more vital to understand its theoretical basis, relational frame theory (RFT). RFT is a psychological theory of human language and cognition, developed by Steven C. Hayes. It focuses on how humans learn language and how language connects them to their environment. In essence, our thoughts, feelings, and behaviors are dependent on our experiences and the context that these experiences provide. Edited by leading relational frame theory (RFT) scholars, Simon Dymond, PhD, and Bryan Roche, PhD, Advances in Relational Frame Theory presents advances in all aspects of RFT research over the last decade, and provides a greater understanding of the core principals of acceptance and commitment therapy (ACT). The book also contains chapters written by Steven C. Hayes and Kelly Wilson, both research-active experts from the RFT community around the world. Because ACT is focused largely on accepting one's thoughts, it is important to understand where these thoughts come from. And while many books on RFT are abstract and require extensive knowledge of behavior analysis, this is the first book to comprehensively but accessibly introduce RFT to ACT mental health professionals. Gaining a deeper knowledge of the relational concepts of RFT can help you understand why a person's behavior does not always match up with their self-professed values. Whether you are a mental health professional, or simply someone who is interested in the connection between language and experience, this book is an invaluable resource."--